Internet Research Ethics - Elgesem, Dag; Ess, Charles; Larsson, Anders Olof; Lüders, Marika; Prabhu, Robindra; Segadal, Katrine Utaaker; Staksrud, Elisabeth; Steen-Johnsen, Kari; Enjolras, Bernard; Fossheim, Hallvard; Ingierd, Helene; Fossheim, Hallvard; et al. (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2015)
This anthology addresses ethical challenges that arise within the field of Internet research. Among the issues discussed in the book are the following: When is voluntary informed consent from research subjects required in using the Internet as a data source? How may researchers secure the privacy of research subjects in a landscape where the traditional public/private distinction is blurred and re-identification is a recurring threat? What are the central ethical and legal aspects of Internet research for individuals, groups, and society?
English
Keywords: Society & social sciences; big data; social media; research ethics; internet research; Facebook; Norway; Personal data; Twitter